Molecular biology of the cell (Garland Publishing, Inc, 1983)
The material on molecular genetics has been revised and expanded so that it can be used as a stand-alone text. A new chapter covers pathogens, infection, and innate immunity. Topics include introduction to the cell, basic genetic mechanisms, methods, internal organization of the cell, and cells in their social context.